Melatonin inhibits the expression of vascular endothelial growth factor in pancreatic cancer cells - Lv, Dong; Cui, Pei-Lin; Yao, Shi-Wei; Xu, You-Qing; Yang, Zhao-Xu (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: To investigate the effects of melatonin on cellular proliferation and endogenous vascular endothelial growth factor (VEGF) expression in pancreatic carcinoma cells (PANC-1). Methods: PANC-1 cells were cultured for this study. The secreted VEGF concentration in the culture medium was determined using ELISA method, VEGF production in the tumor cells was detected by immunocytochemistry, and VEGF mRNA expression was determined by RT-PCR. Results: Higher melatonin concentrations significantly inhibited cellular proliferation, with 1 mmol/L concentration exhibiting the highest inhibitory effect (P